Influenza-attributable years of life lost in older adults in a subtropical city in China, 2012–2017: A modeling study based on a competing risks approach. (August 2020) - Hao, Yajing; Huang, Li; Liu, Xuxiang; Chen, Yinzi; Li, Jing; Wang, Xiling
Highlights: The annual influenza-attributable years of life lost (YLL) was highest in the 75–79 years age group. Influenza A(H3N2) virus was associated with higher YLL than influenza A(H1N1) and B viruses. Competing risks should be considered when estimating the YLL of influenza to avoid overestimation. Abstract: Objective: The aim of this study was to estimate influenza-attributable years of life lost (YLL) in older adults in subtropical Hefei, China during the years 2012–2017, based on a competing risks approach. Methods: The quasi-Poisson model was fitted to weekly numbers of all-cause deaths by 5-year age groups for older adults ≥60 years of age. The product of the weekly influenza-like illness consultation rate and the proportion of specimens that tested positive for influenza was taken as the measurement of influenza activity, which was incorporated into the model as an exploratory variable. Excess deaths associated with influenza were calculated by subtracting baseline deaths (setting influenza activity to zero) from fitted deaths. Influenza-attributable YLL accounting for competing risks was estimated using restricted mean lifetime survival analysis. Results: The annual influenza-attributable YLL was highest in the 75–79 years age group (565 per 100, 000 persons, 95% confidence interval 550–580), followed by the 80–84, 70–74, 85–89, 65–69, and 60–64 years age groups. Influenza A(H3N2) virus was associated with higher YLL than A(H1N1) and B viruses. Influenza-attributable YLL accounted for 1.03–1.53% of total YLL, and the proportion would be overestimated to 2.91–7.34% if the traditional Kaplan–Meier method ignoring competing risks was used. Conclusions: Although influenza-associated mortality increased with age, influenza-attributable YLL was found to be highest in the 75–79 years age group.